Research on uplink sum-rate maximization for STAR-RIS assisted batteryless IoT: SDMA versus NOMA - CHEN Yanming; LYU Bin; YANG Zhen; LI Fei (Tongxin xuebao)
To address the limitations of half-space coverage, low information transmission efficiency of RIS assisted batteryless IoT, a STAR-RIS assisted transmission scheme was proposed. Specifically, a STAR-RIS was deployed between the batteryless device (BD) and the access point, facilitating the uplink information transmission from the BD to the access point, thereby achieving full-space network coverage of the BD. To further enhance energy transmission efficiency, energy beamforming was designed at the power station. To this end, the system sum-rate maximization problems for both space division multiple access (SDMA) and non-orthogonal multiple access (NOMA) scenarios were investigated, with jointly optimization of the relection coefficients of the BD, the energy beamforming vector at the base station and the coefficient matrices of the STAR-RIS. For the SDMA scenario, an iterative algorithm based on the block coordinate descent (BCD) framework was proposed to solve the optimization problem. Similarly, to address the non-convexity of the optimization problem in the NOMA scenario, the objective function was transformed to simplify its solution, and another iterative algorithm based on the BCD framework was proposed. Numerical results show the superiorities of the proposed schemes over the benchmark schemes. Moreover, the utilization of the NOMA achieves better performance than the SDMA.